A LITERATUR REVIEW: SUMBANGSIH PERAN MOHAMMAD NATSIR UNTUK INDONESIA: Mohammad Natsir - Mas Rukhin Lubabul huda (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
This research discusses the contribution of Mohammad Natsir's role for Indonesia, which aims to commemorate Mohammad Natsir's services for Indonesia and introduce history to the wider community. The aim of this research is to identify the Muslim figure Mohmmad Natsir as a figure who played an important role in the progress of Islam in Indonesia. In this study, using a library study with a literature review approach by collecting from several sources of articles from the last 10 years in Google Scholar with the keyword "Mohammad Natsir", the researcher found 4 articles that were in accordance with the discussion, namely about Mohammad Natsir's contribution to Indonesia. The results of this research include: 1) Muhammad Natsir's thoughts in Indonesian Political History 1930–1950, 2) M. Natsir's thoughts in the Reform of Islamic Education in Indonesia, 3) Mohammad Natsir's thoughts on Religion and State, 4) The Role of the Integral Motion Proposed by Muhammad Natsir in 1956 for the Integrity of the Unitary State of the Republic of Indonesia. The benefit of this research is to increase knowledge of Islamic figures who play an important role in the progress of the country and in educational reform.